Internalisasi Nilai Moderasi Beragama Melalui Pendidikan Agama Buddha di Sekolah Menengah Pertama Kabupaten Semarang - Sukodoyo, Sukodoyo; Widiyono, Widiyono; Medhacitto, Tri Saputra; Setyaningsih, Setyaningsih (Jurnal Penelitian Agama Hindu, 2024)
The quality of religious moderation in Indonesia is experiencing degradation and a solution needs to be provided. One way to overcome this problem is through internalizing the value of religious moderation. This research is to analyze the benefits of internalizing the value of religious moderation in Buddhist religious education (PAB) in Semarang Regency Junior High Schools. The research method used in this research is qualitative research with a case study approach. The subjects of this research consisted of nine informants consisting of five teachers and four students and were selected based on their role in internalizing the value of religious moderation through Buddhist education. Data collection was carried out using interview techniques, observation, documentation and document study, then the data was analyzed qualitatively using the steps: data reduction, data presentation and drawing conclusions. Data validity is carried out with diligence and triangulation. The research results obtained show that: (1) The educational approach to the value of religious moderation is moral education which produces the ability to appreciate differences in congregations and religions, respect diversity, not be fanatical, live in harmony, tolerance, morals, love, compassion, share happiness, and have a balanced mind; (2) The process of forming religious moderation values through PAB consists of two domains, namely learning methods and material integration; (3) Education on the value of religious moderation in the integration of PAB learning consists of cognitive, affective and psychomoral impacts; and (4) Education in the value of religious moderation as an effort to build character consisting of routine practice through namakkārapatha, samādhi, devotional service and community service. As a focal point, internalizing the value of religious moderation through Buddhist religious education is very necessary in order to maintain the unity and unity of the Indonesian nation whose motto is Bhinneka Tunggal Ika.